Myths and Gender Relations in Short Stories When Mothers Come by Dwi Ratih Ramadhany - Ariani, Ni Komang (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
The short story